2019
DOI: 10.1016/j.dib.2019.104742
|View full text |Cite
|
Sign up to set email alerts
|

Data regarding the influence of Al, Ti, and C additions to as-cast Al0.6CoCrFeNi compositionally complex alloys on microstructures and mechanical properties

Abstract: This brief paper contains raw data of X-ray diffraction (XRD) measurements, microstructural characterization, chemical compositions, and mechanical properties describing the influence of Al, Ti, and C on as-cast Al0.6CoCrFeNi compositionally complex alloys (CCAs). The presented data are related to the research article in reference [1] and therefore this article can be referred to as for the interpretation of the data. X-ray diffraction data presented in this paper are measurements of 2θ versus intensities for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Since 2004, high- and medium-entropy alloys (HEAs and MEAs) have attracted tremendous attention in various scientific fields [1] , [13] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [14] . However, the corresponding research data are not systematically reported in the literature, precluding data mining for further alloy development.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Since 2004, high- and medium-entropy alloys (HEAs and MEAs) have attracted tremendous attention in various scientific fields [1] , [13] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [14] . However, the corresponding research data are not systematically reported in the literature, precluding data mining for further alloy development.…”
Section: Data Descriptionmentioning
confidence: 99%